Tingkat Pengembangan Dan Daya Terima Bolu Kukus BerbahanDasar Tepung Singkong (Manihot esculenta Crantz) YangDisubstitusi Tepung Kacang Hijau (Phaseolus radiatus) - Lilis Kadarwati, Mahmudah, Eni Purwani, SSi., MSi, Rusdin Rauf, STP., MP (2015)
Introduction: Efforts to reduce the consumption of wheat flour in Indonesia were higher by replacing wheat flour with local food is cassava flour and mung bean flour. The nutritional content of cassava flour is almost the same with the flour so that it can be used as a substitute for wheat flour. The green beans have a fairly high nutrient content compared to other nuts. Mix cereal with green beans is a composition that gives a good protein nutritional value, because each provide additional essential amino acids, so it can be developed in the manufacture of products which steamed spongecake. Objective: The purpose of the research was to evaluate the level of development and acceptance of steamed cakes made from cassava flour that substituted mung bean flour. Methods: Substitution of cassava flour and mung bean flour (100:0), (97,5:2,5), (95:5), (92,5:7,5). Data analysis of the level of development and acceptance of steamed sponge using One Way ANOVA statistical test with the significance level of 95% and if there is an influence, it will be continued by using the test of Duncan Multiple Range Test (DMRT). Results: The results indicated that the acceptance of the colors on the substitution of mung bean flour which is most preferred is the substitution of 0%, the aroma of the most preferred in the substitution of 0%, the taste of the most preferred in the substitution of 5%, the texture is slightly favored in substitution 0% and overall the most preferred in the substitution of 2.5%. Steamed sponge development level is affected by the process of mixing the ingredients, steaming process, and mung bean flour substitution. Conclusion: There is no effect of substitution mung bean flour in the manufacture of steamed sponge on the level of development. There is a substitution effect of acceptability on the color, flavor, taste.